KAJIAN AWAL JEJAK PERADABAN DAN ARSITEKTUR MEGALITIK DI KAWASAN UMANG, DATARAN TINGGI GAYO, ACEH (Jurnal Arsitektur ARCADE, 2026)
The Umang area in the Gayo highlands, Aceh, is a cultural landscape that strongly indicates traces of prehistoric (megalithic) civilization of the Gayo people. This study aims to examine the relationship between geological conditions, landscape elements, and human intervention through the analysis of archaeological features and a landscape architecture approach. The research method was carried out through field observations of site locations, spatial orientation, and symbolic motifs found in the area. The results show a series of archaeological features with a linear structure from the valley to the highlands, consisting of split stone platforms in low elevation areas and slate along the path to the mountains. The slate motifs in the form of various circular patterns indicate symbolic and ritual functions in the area. The absence of traces of permanent habitation, along with the geological conditions of steep slopes and traces of large landslides on the northern side of the area, strengthens the hypothesis that Umang was a ritual site or pilgrimage route, not a residential area. The past community is thought to have been aware of the dangers of natural disasters and created patterns of adaptation to their settlement space. Cosmological understanding is evident in the slate path that climbs from East to West towards the sacred mountain. From a landscape architecture perspective, the lower courtyard functions as a communal space, while the slate path becomes a spiritual transitional space.
Keywords: Gayo, Prehistory, landscape archaeology, cosmology, ritual sites.